Airway fibroepithelial polyposis. (2017) - Labarca, Gonzalo; Caviedes, Ivan; Vial, Macarena R.; Pires, Yumay; Folch, Erik; Majid, Adnan; Fernandez-Bussy, Sebastian
Abstract: Fibroepithelial polyps are benign lesions, frequently found in the skin and genitourinary tract. Airway involvement is rare, and few case reports have been published. Our patient was a 79 y.o. male smoker, who was referred to us with a 3-month history of dry cough. At physical examination, the patient looked well, but a chest CT showed a 6-mm polyp lesion in his trachea. A flexible bronchoscopy confirmed this lesion, and forceps biopsies were performed. Argon plasma coagulation was used to completely resect and treat the lesion. Pathological analysis revealed a fibroepithelial polyp (FP). The aim of this manuscript is to report a case of FP with bronchoscopic management and to review the current literature about this condition.